2021
DOI: 10.1108/gs-05-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of smart senior care service platform in China based on grey relational analysis and Fuzzy-QFD

Abstract: PurposeSmart senior care industry in China currently faces a series of practical difficulties such as an imbalance in the demand and supply structure, service products unable to cater to the actual needs of the elderly and a low degree of marketization. This study therefore proposes using grey relational analysis and the Fuzzy-quality function development (QFD) quality improvement method to help solve these problems.Design/methodology/approachThe proposed method converts the fuzzy requirements of the elderly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Dong, M. and other researchers analyzed the Qingdao senior livable community to study the governance mechanism of complex interests, and the results of the study showed that the cooperation between the government and the capital to build the senior living community can help to alleviate the financial pressure, but it needs to be very attentive and cautious about the complex interests [20]. Xu, Y. W. Y. constructed a smart, safe, and reliable evaluation index system for the quality of smart community pension services to guarantee the services of smart pensions, and took four cities in Jiangsu Province as the research object to test the proposed evaluation method, and the test results confirmed the feasibility and reliability of this method, and the above research helps to standardize the pensioned services [21]. Zhao, Q. and other researchers analyze the benefits of the basic pension system based on the theoretical development of pension adequacy.…”
Section: Introductionmentioning
confidence: 77%
“…Dong, M. and other researchers analyzed the Qingdao senior livable community to study the governance mechanism of complex interests, and the results of the study showed that the cooperation between the government and the capital to build the senior living community can help to alleviate the financial pressure, but it needs to be very attentive and cautious about the complex interests [20]. Xu, Y. W. Y. constructed a smart, safe, and reliable evaluation index system for the quality of smart community pension services to guarantee the services of smart pensions, and took four cities in Jiangsu Province as the research object to test the proposed evaluation method, and the test results confirmed the feasibility and reliability of this method, and the above research helps to standardize the pensioned services [21]. Zhao, Q. and other researchers analyze the benefits of the basic pension system based on the theoretical development of pension adequacy.…”
Section: Introductionmentioning
confidence: 77%
“…Using the "5A" theoretical analysis framework of Penchansky and Thomas, Hu et al established an evaluation system consisting of three primary indicators, including the of home based community care, institutional care, and administrative services [33]. Xu et al construct a quality evaluation indicator system aimed at smart community service for the aged, and the feasibility of the method has been verified in four typical cities in Jiangsu Province [34]. Li et al put forward a model of multi-dimension concentration convolutional neural networks to reflect pension services objectively and accurately [35].…”
Section: Research Hotspotsmentioning
confidence: 99%
“…Studies on the assessment of smart communities are underway. Existing research covers many aspects, such as sustainable development [15,16], service quality of smart communities [17][18][19], intelligent transportation [20], smart home technologies [3,21], and community safety [22,23]. Similarly, research on the sense of gain is now gradually increasing.…”
Section: Introductionmentioning
confidence: 99%